2018
DOI: 10.1002/jsde.12221
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amide Bonds and Aromatic Rings on the Surface Properties and Antimicrobial Activity of Cationic Surfactants

Abstract: The cationic surfactants containing aromatic rings and amide bonds, N,N-dimethyl-N-dodecyl-2-pyrimidinylcarbamoylmethyl ammonium chloride (a), N,N-dimethyl-N-dodecyl-2-thiazolylcarbamoylmethyl ammonium chloride (b), and N,N-dimethyl-N-dodecylphenylcarbamoylmethyl ammonium chloride (c), were synthesized and characterized. The surface tension and conductivity values were employed to investigate the absorption and micellization behavior of the three cationic surfactants. The results showed that the synthesized su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…The replacement of benzyl in BnC 11 P(Ph) 3 Br with metronidazole in MTZC 11 P(Ph) 3 Br caused an additional increase in cmc. He et al, 2019 observed a similar behavior when phenyl was replaced with a heterocycle (thiazole, pyrimidine) in the polar head group of the investigated surfactants. Heterocyclic surfactants had higher values of cmc than the hydrocarbon analogues.…”
Section: Resultssupporting
confidence: 56%
“…The replacement of benzyl in BnC 11 P(Ph) 3 Br with metronidazole in MTZC 11 P(Ph) 3 Br caused an additional increase in cmc. He et al, 2019 observed a similar behavior when phenyl was replaced with a heterocycle (thiazole, pyrimidine) in the polar head group of the investigated surfactants. Heterocyclic surfactants had higher values of cmc than the hydrocarbon analogues.…”
Section: Resultssupporting
confidence: 56%
“…Indeed, quaternary ammonium amphiphiles are well-known for their antibacterial (especially toward Gram-positive) and antifungal activities, which is why they are available as marketed products for a wide range of applications, including pharmaceuticals and cosmetics. Different modifications have been proposed to enhance the antimicrobial activity of these amphiphiles, including addition of alkyl or benzyl groups and different aromatic moieties [21,22]. The modification by the addition of N -benzyl groups is quite common and these surfactants are present in many of the commercial products (e.g., benzalkonium chloride) as disinfectants or biocides [23].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of amide bonds and aromatic rings on the surface properties and antimicrobial activity of N,N‐dimethyl‐N‐dodecyl‐2‐pyrimidinylcarbamoylmethyl ammonium chloride (a), N,N‐dimethyl‐N‐dodecyl‐2‐thiazolylcarbamoylmethyl ammonium chloride (b), and N,N‐dimethyl‐N‐dodecyl‐phenylcarbamoylmethyl ammonium chloride (c) were analyzed and compared with N,N‐dimethyl‐N‐dodecyl‐N‐benzyl ammonium chloride (BAC‐12) of the same alkyl chain length. These surfactants exhibited a high surface ability and better antibacterial activity compared with BAC‐12 (He et al, 2019). We report herein the characterization and biocidal activity against SRB of surfactants para ‐amino‐N‐((1‐decylpyridin‐1‐ium bromide)‐4‐yl) benzamide and para‐amino‐N‐((1‐dodecylpyridin‐1‐ium bromide)‐4‐yl) benzamide (P10 and P12, respectively), P10‐coated AgNP and P12‐coated AgNP, which were prepared according to our pervious publication (Supporting information Appendix S1; Azzam et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%